Association of genetic variants and the susceptibility to abnormal involuntary movements and tardive dyskinesia (TD) in Xhosa schizophrenia patients - Hitzeroth, Angelika (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Genetics))—University of Stellenbosch, 2007.